Insects. Part K [electronic resource] : insect life in the western Arctic coast of America - Johansen, Frits.; Canadian Arctic Expedition (1913-1918) (Ottawa : T. Mulvey, 1921)
Original issued in series: Report of the Canadian Arctic Expedition, 1913-1918 v. 3., pt. K. Includes list of titles in the series. Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44